2016
DOI: 10.1007/s12028-016-0297-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Versus Late Tracheostomy or Prolonged Intubation in Critically Ill Patients with Acute Brain Injury: A Systematic Review and Meta-Analysis

Abstract: Performing an early tracheostomy in acutely brain-injured patients may reduce long-term mortality, duration of mechanical ventilation, and ICU length of stay. However, waiting longer leads to fewer tracheostomy procedures and similar short-term mortality. Future research to explore the optimal timing of tracheostomy in this patient population should focus on patient-centered outcomes including patient comfort, functional outcomes, and long-term mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 53 publications
5
78
3
3
Order By: Relevance
“…There continues to be controversy regarding the optimal timing of TT. Performing an early TT in neurologic ICU patients may reduce long-term mortality, duration of ventilation, and ICU-LOS [27]. In an earlier study, Koh et al [28] even reported that patients undergoing elective tracheostomies at earlier time points had shorter ICU stays compared with patients who were given extubation trials before TT.…”
Section: Discussionmentioning
confidence: 99%
“…There continues to be controversy regarding the optimal timing of TT. Performing an early TT in neurologic ICU patients may reduce long-term mortality, duration of ventilation, and ICU-LOS [27]. In an earlier study, Koh et al [28] even reported that patients undergoing elective tracheostomies at earlier time points had shorter ICU stays compared with patients who were given extubation trials before TT.…”
Section: Discussionmentioning
confidence: 99%
“…The number needed to treat for an additional beneficial outcome (NNTB) was around 11. Also, the probability of discharge from the ICU was higher at day 28 (14). However, the timing (early versus late) TT placement is controversial.…”
Section: Resultsmentioning
confidence: 99%
“…Placement of a TT also allows for direct access to the airway and improved suctioning from the lower airways (11). In addition, data suggests that patients are more comfortable with TT than with endotracheal intubation (12), allowing for earlier discontinuation of analgesia and sedation, which is helpful in facilitating patients to awaken, be weaned from ventilation, and begin early mobilization regimens (13,14).…”
Section: Evidenced-based Clinical Problem Solving Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In subarachnoid hemorrhage patients, performing early (days 1–7) versus later (days 8–20) tracheostomy resulted in less pneumonia, less respiratory adverse events, shorter duration of mechanical ventilation, and ultimately earlier decannulation [9]. In an analysis of 10 trials in acute brain injured patients, early tracheostomy was found to reduce long-term mortality, duration of mechanical ventilation, and ICU length of stay; however delaying tracheostomy resulted in an increased probability of not needing a tracheostomy [10]. Assessing need for tracheostomy at day 7 has been recommended [11].…”
Section: Discussionmentioning
confidence: 99%